Pengaruh efikasi diri siswa terhadap hasil belajar ekonomi dalam pembelajaran daring - Nur Fadilah, Reny; Arief Rafsanjani, Mohamad (Jurnal Paradigma Ekonomika, 2021)
In response to the Covid-19 pandemic, the Ministry of Education, through circular letter number 4 of 2020, notifies that the learning process is carried out from home through online learning. The time allocation carried out in online learning during the pandemic is shorter than the previous conventional learning. In the learning process, academic self-efficacy is very important. Through clear goals and self-confidence, academic self-efficacy can determine the success of academic behavior in the future. This article describes the research results on the effect of student self-efficacy on student learning outcomes in class X IPS SMAN 1 Sidoarjo on economics subjects in online learning. This type of research is explanatory and uses a quantitative approach. The population in this study was 109 students of class X Social Sciences at SMA Negeri 1 Sidoarjo. In comparison, the sample in this study was 85 students selected using a simple random sampling technique. Data collection techniques used are questionnaires and documentation. The data analysis technique used in this research is descriptive statistical analysis, which includes prerequisite analysis tests (normality test and linearity test) and simple regression analysis. This study indicates that the self-efficacy of class X IPS students at SMA Negeri 1 Sidoarjo does not affect economic learning outcomes in online learning. Â